A Case Study in Mitigating COVID-19 Inequities through Free Textbook Implementation in the U.S. Issue 1 (8th September 2021) - Williams, Katherine; Werth, Eric
COVID-19, in addition to disrupting the global education system in general, is widening the economic and racial gaps institutions have spent years trying to address. The economic reality is that students who work to support themselves, their families, and purchase educational materials needed to succeed have been disproportionately harmed. This article discusses how the global COVID-19 pandemic is compounding structural inequities inherent in higher education. This requires faculty to reevaluate their role as agents of change in a world that is fundamentally different than it was a short time ago. The experience of one liberal arts institution in the U.S. who moved all courses to free materials in under six months will be recounted as an example of what is possible during extraordinary circumstances if students are truly prioritized during strategic planning.